A Red‐Emitting Luminescent Material Capable of Detecting Low Water Content in Organic Solvents. Issue 35 (26th July 2016) - Wang, Tianren; Li, Huanrong
Abstract: A new red‐emitting luminescent material was prepared from a gel formed by simply mixing EuCl3 ⋅ 6 H2 O and 4′‐ para ‐phenylcarboxyl‐2, 2′:6′, 2′′‐terpyridine (Hcptpy) in a molar ratio of 1:2 in anhydrous ethanol at room temperature. It shows bright red luminescence dominated by the 5 D0 → 7 F2 transition of Eu 3+, a long lifetime (1.16 ms), a high absolute quantum yield (48.2 %), and good thermostability (stable up to 500 °C). In addition, the luminescence of the material can be easily quenched by contact with water, which makes it suitable for detecting low contents of water (0.1–1.5 vol %) in common organic solvents such as diethyl ether and THF. Abstract : Water detector : A bright red‐emitting luminescent material prepared from a gel formed by simply mixing EuCl3 ⋅ 6 H2 O and 4′‐ para ‐phenylcarboxyl‐2, 2′:6′, 2′′‐terpyridine in anhydrous ethanol at room temperature shows great potential in the detection of low‐content water in diethyl ether and THF by means of luminescence quenching (see figure).